Implementasi Pasal 28 Ayat 1 Undang-Undang Nomor 1 Tahun 2024 Tentang Informasi Dan Transaksi Elektronik Dalam Tindak Pidana Penipuan Jual Beli Online (Studi Kepolisian Resort Kota Pangkalpinang) - Fayis Dega Adriansah; Toni Toni; Dr. Rio Armanda Agustian, S.H.,M.H (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The implementation of this research is the implementation of Article 28 Paragraph 1 of the Law on Information and Electronic Transactions in handling criminal acts of online fraud. The formulation of the research problem analyzes the implementation of Article 28 Paragraph 1 of the ITE Law Number 1 of 2024 at the Pangkalpinang Resort Police, and the obstacles faced by the Pangkalpinang Resort Police in implementing the Article. The purpose of the research is to identify operational constraints, evaluate the effectiveness of law enforcement mechanisms, and public trust in digital transactions in the modern era. The research method is an empirical method, with a sociological approach. Research data was collected through observations at the research location and interviews, as well as analysis of legal materials using qualitative descriptive analysis techniques. The results of the study explain that the implementation of Article 28 Paragraph 1 of the ITE Law Number 1 of 2024 has been carried out in accordance with the Standard Operating Procedure at the Pangkalpinang Resort Police through an effective investigation and inquiry process. There are internal constraints such as technological limitations, lack of investigator resources, difficulty in obtaining witness statements, and fraudsters who are difficult to detect because they use fake identities. The low level of digital literacy in society and the absence of strict rules for online supervision are also external obstacles. To overcome these obstacles, the Pangkalpinang Police have made preventive efforts to socialize digital literacy to the public, put up online fraud banners, and take repressive measures in collaboration with banks and the Ministry of Communication and Digital Affairs. Keywords: Implementation, Criminal Act, Fraud, Selling Buying Online